The Effects of Surface Mechanical Deformation and Bovine Serum Albumin on the Tribological Properties of Polyvinyl Alcohol Hydrogel as an Artificial Cartilage - Feng Li; Gang Zhang; Anmin Wang; Feng Guo (Advances in Materials Science and Engineering)
The mechanical and tribological properties of polyvinyl alcohol hydrogel as an artificial cartilage were studied under water and bovine serum albumin-lubricated sliding conditions. The frictional properties of the polyvinyl alcohol hydrogel were investigated via reciprocating frictional tests. The effect of surface mechanical deformation on the tribological properties of the polyvinyl alcohol hydrogel as an artificial cartilage was studied by concurrently recording the z-axis displacement and friction coefficient time. Three different factors were chosen including load, speed, and lubrication. The results showed that the albumin solution could reverse the trend in the coefficient of friction in tests at different loading levels. There was no improvement in the friction condition in albumin at low speeds. However, when the speed was increased to 2 Hz, the coefficient of friction was significantly reduced. Wear testing was also conducted, and wear tracks were found on the sample surface. The results also showed that even though the surface deformation could recover as the water phase of the porous structure recovered, the coefficient of friction continued to increase simultaneously. This relationship between mechanical and frictional tests indicated that biphasic lubrication effects may not be the only dominant factor underlying the excellent friction properties of polyvinyl alcohol hydrogel.